Penerapan Pembelajaran Tahfidzul Al-Qur’an untuk Meningkatkan Kecerdasan Spiritual Siswa di MTs Teladan Gebang - Putri Ramayani; Muhammad Saleh; Fauzan Azmi (Transformasi Manageria: Journal of Islamic Education Management, 2021)
This research is motivated by a phenomenon that occur in schools where most of the students have high intellectual intelligence and emotional intelligence but do not have good morals. Thus, through tahfidz learning, they are expected to be able to realize that spiritual intelligence is important for their morals so that they can growup to be a generation that has good potential and also good morals. Based on this background, the writer wishes to discuss it in his thesis and take the title of tahfidzqur'an learning to improve students' spiritual intelligence at MTs Exampel Gebang. This research focused on:(1) How is the concept of tahfidzqur'an learning to improve the spiritual intelligence of students at MTs Exampel Gebang? (2) How is the implementation of tahfidzqur'an learning to improve students' spiritual intelligence at MTs Exampel Gebang? (3) How is the implications of tahfidzqur'an learning to improve students' spiritual intelligence at MTs Exampel Gebang. The purposes of this researchare (1) To describe the concept of tahfidzqur'an learning to improve the spiritual intelligence of students at MTs Exampel Gebang; (2) To describe the implementation of tahfidzqur'an learning to improve students' spiritual intelligence at MTs Exampel Gebang; (3) To describe the implications of tahfidzqur'an learning to improve students' spiritual intelligence at MTs Exampel Gebang. This research uses a qualitative approach. The data collection technique uses observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and data verification. Check the validity of the data using extension of participation, observer perseverance, and triangulation. The results of the research are (1) The concept of tahfidzqur'an learning aims to train students to love the Qur'an and become a superior person from within themselves in the form of personality and spiritual intelligence; (2) The implementation of tahfidz learning includes arranging sincere intentions, with parental permission, diligent and patient in memorizing, leaving any immorality behind and keep away from harm. There are two methods used by the tahfidz teacher, namely the bin nadzar method and the murajaah method; (3) The implications of tahfidzqur'an learning make students have a high sense of empathy and always be grateful.